Isospin equilibration phenomenon and mid-rapidity IMF emission in the 48Ca +27Al 40 MeV/nucleon collision. (December 2020) - Papa, M; Acosta, L; Cardella, G; Filippo, E De; Favela, F; Geraci, E; Gnoffo, B; Lanzalone, G; Maiolino, C; Martorana, N S; Pagano, A; Pagano, E V; et al.
Abstract: It is discussed the dynamics of Isospin equilibration in reactions involving the production of Intermediate Mass Fragment (IMF) in the mid-rapidity region. The investigation proceeds through the measurements of the reduced value of the total dipolar signal obtained from the measured velocities and charges of all fragments produced in the collision 48 Ca + 27 Al at 40 MeV/nucleon. Preliminary experimental results, along with the comparison with CoMD-III model calculations for different density functionals related to the symmetry energy, are presented.